The Implementation of Law No: 24 of 2009, Concerning the Flag, Language, National Emblem and National Anthem for Students of SMPS 8 Alwashliyah - Zahara, Siti Fatimah; Putri, Jihan Hidayah; Prihatini, Syafrina (PT Inovasi Pratama Internasional, 2024)
The community service program partners are students from Alwashliyah 8 Medan Middle School. The background is the law regarding the flag, language and national symbols, as well as the national anthem. The red and white flag, the Indonesian language Garuda Pancasila, and the national anthem Indonesia Raya are the national identity and identity of the unitary Republic of Indonesia. These four symbols are a reflection of the country's sovereignty in relations with other countries. The main target in this activity is the implementation of Law N0. 24 of 2009 for students at SMP Alwashliyah 8 Medan with the theme